Hypercapnic warm-up and re-warm-up-A novel experimental approach in swimming sprint - Danek, N.; Szczepan, S.; Wróblewska, Z.; Michalik, K.; Zaton, M. (PLOS ONE, 2025)
The purpose of this study was to determine the effective warm-up protocol using an added respiratory dead space (ARDS) 1200 ml volume mask to determine hypercapnic conditions, on the swimming velocity of the 50 m time trial front crawl. Eight male members of the university swimming team, aged 19-25, performed three different warm-up protocols: 1) standardized warm-up in water (WUCON); 2) hypercapnic warm-up in water (WUARDS); 3) hypercapnic a 20-minute transition phase on land, between warm-up in water and swimming test (RE-WUARDS). The three warm-up protocols were implemented in random order every 7th day. After each protocol, the 50 m time trial front crawl swimming (swimming test) was performed. The fastest time trial swimming of 50 m front crawl was achieved after the hypercapnic transition phase (RE-WUARDS) protocol and was 27.5 ± 1.6 seconds, 1.2% faster than hypercapnic warm-up protocol (p = 0.01). This result was confirmed by a higher swimming average speed of the exercise test after RE-WUARDS compared to WUARDS (p = 0.01). The use of ARDS provoked a state of tolerable hypercapnia (obtaining carbon dioxide concentration in arterialized blood pCO2 > 45 mmHg) achieving a post-warm-up of WUARDS value 49.7 ± 5.9 mmHg (compared to the control condition which was a statistically significant difference p = 0.02) and before time trial RE-WUARDS 45.7 ± 2.1 mmHg (p = 0.01 compared to WUCON). After breathing through the 1200 ml ARDS mask during the 20-minute re-warm-up phase, there was a trend of faster time trial among participants compared to the control condition, and statistically significantly faster times compared to WUARDS, indicating that further study is appropriate to verify the efficacy of the proposed method to improve swimming efficiency.